Effects of Lactate Administration on Mitochondrial Respiratory Function in Mouse Skeletal Muscle - Takahashi, Kenya; Tamura, Yuki; Kitaoka, Yu; Matsunaga, Yutaka; Hatta, Hideo (Frontiers in Physiology, 2022)
Recent evidence has shown that mitochondrial respiratory function contributes to exercise performance and metabolic health. Given that lactate is considered a potential signaling molecule that induces mitochondrial adaptations, we tested the hypothesis that lactate would change mitochondrial respiratory function in skeletal muscle. Male ICR mice (8 weeks old) received intraperitoneal injection of PBS or sodium lactate (1 g/kg BW) 5 days a week for 4 weeks. Mitochondria were isolated from freshly excised gastrocnemius muscle using differential centrifugation and were used for all analyses. Lactate administration significantly enhanced pyruvate + malate- and glutamate + malate-induced (complex I-driven) state 3 (maximal/ATP synthesis-coupled) respiration, but not state 2 (basal/proton conductance) respiration. In contrast, lactate administration significantly decreased succinate + rotenone-induced (complex II-driven) state 3 and 2 respiration. No significant differences were observed in malate + octanoyl-l-carnitine-induced state 3 or 2 respiration. The enzymatic activity of complex I was tended to increase and those of complexes I+III and IV were significantly increased after lactate administration. No differences were observed in the activities of complexes II or II+III. Moreover, lactate administration increased the protein content of NDUFS4, a subunit of complex I, but not those of the other components. The present findings suggest that lactate acts as a signaling molecule that alters mitochondrial respiratory function in skeletal muscle.